DESAIN MARKETING CAPABILITIES PADA MIGRANT ENTREPRENEUR USAHA JASA “PANGKAS RAMBUT MADURA” - Andi - Setiawan; Rustono - Rustono; Sri - Wahyuni; Rif'ah Dwi Astuti (Politeknik Negeri Semarang, 2018)
The challenge of the Madura Hair Haircut Entrepreneurs in the barber industry is not small. The problem of competition in urgent Hair Haircut business industry must be investigated is the knowledge and improvement of marketing capability. Marketing capabilities is one model design that offers problem solving for Madura haircut business. Furthermore, this research proposes the problem of research that is How a structural modeling model describes the marketing capabilities of Madura haircutting business in the face of competition in the barber industry. The sampling technique used in this research is accidental sampling method in this case is Madura haircutting business in Central Java, especially Semarang and surrounding areas. As for the number of sample research is 100 samples. This research technique will use two approaches: 1). Confirmatory factor analysis, on Structural Equation Modeling (SEM); and 2). Regression Weight in Structural Equation Modeling (SEM). The model outline in this research can give positive contribution to Madura haircut business in order to realize competitive advantage, in the form of suggestions of managerial implications and the formulation of the marketing science. The managerial advice is aimed at Madura haircut business in formulating a management policy of competitive advantage in the future.